Age-Related Changes of the Anticipatory Postural Adjustments During Gait Initiation Preceded by Vibration of Lower Leg Muscles - Kimijanová, Jana; Bzdúšková, Diana; Hirjaková, Zuzana; Hlavačka, František (Frontiers in Human Neuroscience, 2021)
Gait initiation (GI) challenges the balance control system, especially in elderly. To date, however, there is no consensus about the age effect on the anticipatory postural adjustments (APAs). There is also a lack of research on APAs in older adults after proprioceptive perturbation in the sagittal plane. This study aimed to compare the ability of young and older participants to generate the APAs in response to vibratory-induced perturbation delivered immediately before GI. Twenty-two young and twenty-two older adults performed a series of GI trials: (1) without previous vibration, (2) preceded by vibration of triceps surae muscles, and (3) preceded by vibration of tibialis anterior muscles. The APAs magnitude, velocity, time-to-peak, and duration were extracted from the center of pressure displacement in the sagittal plane. Young participants significantly modified their APAs during GI, whereas older adults did not markedly change their APAs when the subjective vertical was shifted neither backward, nor forward. Significant age-related declines in APAs were observed also regardless of altered proprioception. The results show that young adults actively responded to altered proprioception from lower leg muscles and sensitively scaled APAs according to the actual position of body verticality. Contrary, older adults were unable to adjust their postural responses indicating that the challenging transition from standing to walking probably requires higher reliance on visual input. The understanding of age-related differences in APAs may help to design training programs for elderly specifically targeted to improve balance control in different sensory conditions, particularly during gait initiation.